Consumer Perspectives on a Pericoital Contraceptive Pill In India and Uganda - Cover, Jane K.; Drake, Jennifer K.; Kyamwanga, Imelda T.; Turyakira, Eleanor; Dargan, Tanya; Kumakech, Edward; Harner-Jay, Claudia (International perspectives on sexual and reproductive health, 2013)
Studies suggest that women in some countries have adopted emergency contraceptive pills as a routine method of family planning. This practice indicates there may be latent demand for a pericoital contraceptive pill taken only when a woman has sexual intercourse, and labeled and marketed for use as a regular contraceptive method. METHODS: To understand the appeal and potential market for a pericoital contraceptive pill, 39 focus groups and 23 in-depth interviews were conducted with women and men in Lucknow, Uttar Pradesh, India, and Kampala, Uganda. A total of 281 individuals participated in this qualitative study. RESULTS: In general, women embraced the idea of a female-controlled method that would be easier than taking a daily oral contraceptive pill and that could be taken either before or after sexual intercourse; in Uganda, especially, women approved of the fact that the method could be taken without a partner's knowledge. Although we do not yet know the extent of side effects for this method, women expressed some concerns about the level and nature of potential side effects. CONCLUSIONS: The results suggest that a pericoital contraceptive pill would be well-received by consumers in both country settings. If its efficacy and side effects are acceptable, a pericoital contraceptive pill could fill a gap for female-controlled, discreet, coitus-related contraception, particularly among women who do not have sex very frequently.
Keywords: pericoital; contraceptive pill; Uganda; India